FORMAÇÃO PARA O ENSINO DE DANÇA: pensamento de professores - Luciana Rosa Gualda (Revista Diálogo Educacional, 2008)
The search for aesthetics and technical perfection makes dance loose its expression sense and turn into pure mechanical execution of movements, destroying, this way, the possibility of freedom and also limiting the students' imaginative and creative capacities. Some professionals propose the teaching of dance based on reflection and defend that the body should be seen as a rich source of knowledge that, when not regarded as an object, can be the place where critical reflection happens. Such approach implies the rupture with technical inflexibility in favor of the search for both a state of freedom in dance and respect to the diversity of bodies. Five teachers with recognized experience in such a way of teaching dance were interviewed so that their conception regarding teaching and the work with the body could be analyzed. If on the one hand the interviewed teachers believe that teacher education is important for their formation, on the other researchers claim that the dance teachers are not prepared to act in schools. This article proposes further discussion and reflection about the teaching of dance, having as its is main focus the view that such teaching should always aim at the development of creativity and expression capacity in order to reach a bigger proximity between Education and dance as far as teacher formation is concerned, as well as a greater valorization of the teaching of dance in regular schools.